2022
DOI: 10.1167/jov.22.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Crystal or jelly? Effect of color on the perception of translucent materials with photographs of real-world objects

Abstract: Translucent materials are ubiquitous in nature (e.g. teeth, food, and wax), but our understanding of translucency perception is limited. Previous work in translucency perception has mainly used monochromatic rendered images as stimuli, which are restricted by their diversity and realism. Here, we measure translucency perception with photographs of real-world objects. Specifically, we use three behavior tasks: binary classification of “translucent” versus “opaque,” semantic attribute rating of perceptual qualit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…Meanwhile, the material attributes perceived by the observers are highly positively correlated with one another for both real photographs and generated images of soaps (Figure 3(c)). The correlation among the attributes are in agreement with our previous empirical findings 12 . Figure 3(d) shows examples of real and generated images judged to have various degrees of translucency similar to that of real photographs.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Meanwhile, the material attributes perceived by the observers are highly positively correlated with one another for both real photographs and generated images of soaps (Figure 3(c)). The correlation among the attributes are in agreement with our previous empirical findings 12 . Figure 3(d) shows examples of real and generated images judged to have various degrees of translucency similar to that of real photographs.…”
Section: Resultssupporting
confidence: 92%
“…We also discover the intricate role of color in translucent appearance. Most of the previous works explored the effect of color on material perception and recognition by manipulating the color/luminance distribution of material images 12,21,63,70,111,112 . For example, converting color translucent images to grayscale ones decreases perceived translucency 12,21,63,71 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such estimation errors have provided useful information as to what kind of image cues humans use to estimate gloss. A significant number of psychophysical studies have been carried out not only on gloss but also on other optical material properties (e.g., translucency, transparency, wetness) ( Fleming & Bulthoff, 2005 ; Motoyoshi, 2010 ; Xiao et al., 2014 ; Sawayama, Adelson, & Nishida, 2017 a, Liao, Sawayama, & Xiao, 2022 ) and mechanical material properties (e.g., viscosity, elasticity) ( Kawabe, Maruya, Fleming, & Nishida, 2015 ; Paulun et al., 2017 ; van Assen, Barla & Fleming, 2018 ; van Assen, Nishida, & Fleming, 2020 ). Neurophysiological and neuroimaging studies have revealed various neural mechanisms underlying material perception ( Kentridge, Thomson, & Heywood, 2012 ; Nishio, Goda, & Komatsu, 2012 ; Nishio, Shimokawa, Goda, & Komatsu, 2014 ; Miyakawa et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%